Child soldiers: theory and reality of their existence: the question of international protection available to them in contemporary times - Massey, Chitralekha Marie (2000)
Children are regarded as holders of specific rights and special privileges, and yet more and more children continue to be abused in one form or the another. One of the worst forms of abuse is the willingness of adults today to use children on the numerous frontlines of the world. This aim of this thesis is to develop an argument against the practice of child recruitment and participation and for the practice of non-recruitment and hence non-participation in any form of all children under 18 in armed conflicts.